Nursing Care in Hallucination Patients - Moulisya, Deca Gardena; Firnanda, Dhea Lyra (Yayasan Rumah Ilmu Professor, 2023)
The aim of this study was to examine the implementation of nursing care for two patients who experienced hallucinatory sensory perception disorders. The research method uses a case study approach with data analysis through medical records, observations, and interviews with patients and families. The results showed that both patients experienced sensory perception disorders in the form of auditory hallucinations. The initial assessment includes identification of mental health history, observation of hallucinatory behavior, and precipitating factors. The nursing diagnosis was determined as sensory perception disorder: hallucinations. The treatment plan involves collaboration with the mental health team, use of drug therapy prescribed by the doctor, as well as nursing interventions such as education about stress management, distraction techniques, and increased coping. Evaluations are carried out periodically to monitor the patient's response to the interventions provided. The conclusion of this study is that nursing care for patients with sensory perception disorders requires a comprehensive approach that includes collaboration between nurses, mental health teams and families in order to help improve the quality of life of patients with sensory perception disorders, especially in managing the symptoms of hallucinations.